2020
DOI: 10.3897/neobiota.60.56117
|View full text |Cite
|
Sign up to set email alerts
|

Germination of the invasive legume Lupinus polyphyllus depends on cutting date and seed morphology

Abstract: In semi-natural grasslands, mowing leads to the dispersal of species that have viable seeds at the right time. For invasive plant species in grasslands, dispersal by mowing should be avoided, and information on the effect of cutting date on the germination of invasive species is needed. We investigated the germination of seeds of the invasive legume Lupinus polyphyllus Lindl. depending on the cutting date. We measured seed traits associated with successful germination that can be assessed by managers for an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Larger stands that need to be mown with mowing machinery can also be mown after full bloom of L. polyphyllus as long as the seeds are green and soft. What should be avoided in any case is the dispersal of ripe L. polyphyllus seeds (characterized by brown to black color and hardseededness; Klinger et al 2020) by mowing machinery or zoochory. Although another study found that mowing once annually reduced vital rates and biomass of L. polyphyllus (Ramula 2020), this could not be confirmed for the present study area (Klinger et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Larger stands that need to be mown with mowing machinery can also be mown after full bloom of L. polyphyllus as long as the seeds are green and soft. What should be avoided in any case is the dispersal of ripe L. polyphyllus seeds (characterized by brown to black color and hardseededness; Klinger et al 2020) by mowing machinery or zoochory. Although another study found that mowing once annually reduced vital rates and biomass of L. polyphyllus (Ramula 2020), this could not be confirmed for the present study area (Klinger et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The species is very modest with habitat requirements and produces a large amount of durable hard-coated [45] and small (average 4 mm length) seeds. The coloration of seeds is highly variable [46], and the coloration is connected to viability and timing of germination [47]. One inflorescence produces usually a few hundred seeds but can reach up to thousand seeds per plant [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…The germination potential of common, nationally invasive and highly harmful garden lupin (Large-leaved lupin) Lupinus polyphyllus seed was studied to see if seed viability was affected in municipal tunnel or windrow composting processes or in farm-scale or laboratory-scale AD process in mesophilic conditions. Seeds of L. polyphyllus are capable of after-ripening and germinating even if vegetation is mowed in the early phase of seed ripening [47]. Germination potential increases with time, and therefore desiccated and hard seeds may prove to be resistant even in extreme conditions.…”
Section: Introductionmentioning
confidence: 99%
“…If seed viability would decrease significantly within the first 5 years after burial, as suggested by the classification as short‐term persistent, preventing seed shedding could rapidly reduce new germination and establishment events of L. polyphyllus in our study region. Also, the right timing of management actions plays an important role in preventing the incorporation of the seeds into the seed bank, as seeds of L. polyphyllus from meadows being cut early tend to germinate in autumn, seeds from meadows being cut late express higher levels of dormancy, and could potentially accumulate in the soil seed bank (Klinger et al 2020). To this end, early and, if necessary, repeated mowing of the mountain meadows would be crucial.…”
Section: Discussionmentioning
confidence: 99%
“…The management of large parts of the grasslands was optimized for the conservation of T. tetrix , that is meadows were mown later in summer since the early 1990s. This was beneficial for seed ripening of Lupinus polyphyllus (Klinger et al 2020) and may be a reason for the invasion success of this species.…”
Section: Methodsmentioning
confidence: 99%